2021
DOI: 10.1108/ci-04-2021-0073
|View full text |Cite
|
Sign up to set email alerts
|

Risks of water and wastewater PPP projects: an investors’ perspective

Abstract: Purpose Water and wastewater (WW) projects are gaining attention in Iran because of shortages of water resources. However, these projects are lengthy and they are accompanied by numerous risks, such as lack of sufficient financial resources. Public–private partnerships (PPPs) are taken into account as a constructive approach to deal with the problem of insufficient government funds and they are increasingly being implemented to construct the required infrastructures in different countries. Although WW projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…This study's findings have identified the final 21 barriers based on questionnaires, followed by prioritized barriers using mean scores, classified barriers consisted of 5 clusters, ranked strategies to alleviate the barriers and determined execution period. Meanwhile, previous studies have revealed different findings and have not determined the execution period for implementing the barrier-alleviation strategies, such as Amiri et al. (2022), Cao et al.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's findings have identified the final 21 barriers based on questionnaires, followed by prioritized barriers using mean scores, classified barriers consisted of 5 clusters, ranked strategies to alleviate the barriers and determined execution period. Meanwhile, previous studies have revealed different findings and have not determined the execution period for implementing the barrier-alleviation strategies, such as Amiri et al. (2022), Cao et al.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Previous academic works also have identified various risk factors in PPP construction projects in various countries. For example, Amiri et al. (2022) identified 94 critical barriers in Iran's water and waste-water PPP projects with top five barriers include financial-asset injection issue, inflation-rate fluctuation, decision-making weakness, imported-equipment-issue and effect of other projects' uncertain circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many PPP projects suffer from cost/time overruns, both globally (Ramsey and Asmar, 2020) and inside Iran (Heravi and Mohammadian, 2021), which denotes their feeble performance. Previous PPP research in Iran concentrated on PPPs' risk (Amiri et al, 2021), critical success factors in PPP highways (Noorzai et al, 2016;Akbari Ahmadabadi and Heravi, 2019), increasing the VFM (Sobhiyah et al, 2009), PPPs barriers (Sarvari et al, 2021), and negotiation management in PPPs (Attarzadeh et al, 2017). However, the concentration on PPPs' performance management is scarce in this region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many PPP projects suffer from cost/time overruns, both globally (Ramsey and Asmar, 2020) and inside Iran (Heravi and Mohammadian, 2021), which denotes their feeble performance. Previous PPP research in Iran concentrated on PPPs’ risk (Amiri et al. , 2021), critical success factors in PPP highways (Noorzai et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…}DQD x@ ANFIS Q=DN=U [32] "CU= x@ u=oQ@N MU=B R= GQNDUt 'hWm p=tDL= w `wkw p=tDL= 'QF= COW |v=@ R Q}eDt |Oa@xU lU} Q T} QD=t 2 pwOH R= lU} Q |v=@ R Q}eDt xR=Ov= w CU= xt=vVUQB CUO x@ |v=@ R Q}O=kt |R=i pO=at 3 pwOH x@ xHwD =@ TBU "CU= xOt; CUO x@ p=tDL= '`wkw p=tDL= 'QF= COW |OOa Q}O=kt u=oQ@N |= Q@ w s}_vD |irO pw= QwO |xt=vVUQB Oa@ s=o QO "OW |UQQ@ |irO QDsm xm |rt=wa 'u=oQ@N Q_v j@] w u}ov=}t |x@U=Lt j} Q] R= TBU "OW p=UQ= QwO G}=Dv '|irO R= xrLQt Qy QO "OW hPL 'OvOQm|t Ci=} QO = Q R=}Dt= 70 R= swU QwO QO , =D}=yv "OW p=UQ= u=oQ@N |= Q@ Cq= -wU x@ MU=B QO QDW}@ RmQtD |= Q@ p@k `} RwD w p=kDv= |YwYN |DrwO CmQ=Wt |=yxSwQB QO lU} Q pt=a 30 O=OaD "O}UQ Q_v j=iD= w `=tH= x@ ? ; xO=O x=o}=B p}mWD "4"2 xHwD =@ lU} Q u= R}t uOQw; CUO x@ |= Q@ '|R=i |=[i QO w xDWPo C=ar=]t QO pwOH R= |v=@ R Q}eDt ^=Lr R= QwDm=i Qy |= Q@ `wkw p=tDL= w QF= COW Oa@ wO x@ QO =t= 'xOW xO=iDU= [33]15 PMI xSwQB C} Q}Ot wD}DUv= R= |W=v |R=i Q}O=kt xDiQo Q_v QO lU} Q Qy u= R}t |Q}oxR=Ov= |= Q@ R}v hWm p=tDL= Oa@ VywSB u}= x@ &CU= lU} Q `wkw Cra |}=U=vW Qw_vt x@ hWm C}r@=k u}}aD "CU= xOW u; O=ONQ R= p@k lU} Q `wkw x@ uOQ@ |B |}=v=wD 'hWm p=tDL= Qo}O CQ=@a CU= QDsm lU} Q u= R}t 'OW=@ QDW}@ |@=QN l} hWm p=tDL= xJQy [34] "CU= xR=Ov= "OwQ|t QDq=@ lU} Q u= R}t 'OW=@ QDsm |@=QN l} hWm p=tDL= xJQy w QO "Ot; CUO x@ 2 pwOH j} Q] R= |v=@ R Q}eDt ^=Lr R= QwDm=i Qy |= Q@ lU} Q 4 '\UwDt 3 'sm 2 'sm |r}N 1 ? }DQD x@ lU} Q O=Oa= swyit pwOH u}= 'QF= COW |v=@ R |=yxO=O VwQ u}= R= xO=iDU= =@ "CU= O=}R |r}N 5 w O=}R u}= Oa@ |xrLQt QO "OW XNWt pt=a Qy lU} Q w hWm p=tDL= '`wkw p=tDL= O=Oa= R= |R=i x@ |v=@ R |=yxO=O p}O@D |= Q@ "OW p}O@D |R=i |=yxO=O x@ =yxO=O u=Wv 3 pwOH QO |v=@ R |=yQ}eDt u}= R= l} Qy |R=i Q}O=kt w xO=iDU= |FrFt |R=i "CU= xOW xO=O xk]vt RmQt VwQ R= '|FrFt |R=i O=Oa= x@ |v=@ R |=yQ}eDt p}O@D R= TB |R=iQ}e OQmrta u} QDy@ =@ |R=i O=Oa= uOQm |R=i|O |= Q@ [38] QO xm CU=vat u}= x@ 'R |oDU@ty ?}…”
mentioning
confidence: 99%